A role for misaligned gene expression of fetal gene program in the loss of female-specific cardiovascular protection in young obese and diabetic females - Pulakat, Lakshmi (Frontiers in Endocrinology, 2023)
Healthy, premenopausal women have the advantage of female-specific cardiovascular protection compared to age-matched healthy men. However, pathologies such as obesity and Type 2 diabetes mellitus (T2DM) cause losing of this female-specific cardiovascular protection in young, obese and diabetic females. Molecular mechanisms underlying this loss of female-specific cardiovascular protection in young, obese and diabetic females are not clearly elucidated. This review takes a close look at the latest advances in our understanding of sex differences in adult cardiac gene expression patterns in health and disease. Based on the emerging data, this review proposes that female biased gene expression patterns in healthy adult hearts of human and pre-clinical models support the existence of active fetal gene program in healthy, premenopausal female heart compared to age-matched healthy male heart. However, the misalignment of gene expression pattern in this female-specific active cardiac fetal gene program caused by pathologies such as obesity and T2DM may contribute to the loss of female-specific cardiovascular protection in young, obese and diabetic females.